Ex Vivo Drug Susceptibility Testing and Molecular Profiling of Clinical Plasmodium falciparum Isolates from Cambodia from 2008 to 2013 Suggest Emerging Piperaquine Resistance - Suwanna Chaorattanakawee; David Saunders; Darapiseth Sea; Nitima Chanarat; Kritsanai Yingyuen; Siratchana Sundrakes; Piyaporn Saingam; Nillawan Buathong; Sabaithip Sriwichai; Soklyda Chann; Youry Se; Yom You; et al. (2015)
Cambodia's first-line artemisinin combination therapy, dihydroartemisinin-piperaquine (DHA-PPQ), is no longer sufficiently curative against multidrug-resistant Plasmodium falciparum malaria at some Thai-Cambodian border regions. We report recent (2008 to 2013) drug resistance trends in 753 isolates from northern, western, and southern Cambodia by surveying for ex vivo drug susceptibility and molecular drug resistance markers to guide the selection of an effective alternative to DHA-PPQ. Over the last 3 study years, PPQ susceptibility declined dramatically (geomean 50% inhibitory concentration [IC50] increased from 12.8 to 29.6 nM), while mefloquine (MQ) sensitivity doubled (67.1 to 26 nM) in northern Cambodia. These changes in drug susceptibility were significantly associated with a decreased prevalence of P. falciparum multidrug resistance 1 gene (Pfmdr1) multiple copy isolates and coincided with the timing of replacing artesunate-mefloquine (AS-MQ) with DHA-PPQ as the first-line therapy. Widespread chloroquine resistance was suggested by all isolates being of the P. falciparum chloroquine resistance transporter gene CVIET haplotype. Nearly all isolates collected from the most recent years had P. falciparum kelch13 mutations, indicative of artemisinin resistance. Ex vivo bioassay measurements of antimalarial activity in plasma indicated 20% of patients recently took antimalarials, and their plasma had activity (median of 49.8 nM DHA equivalents) suggestive of substantial in vivo drug pressure. Overall, our findings suggest DHA-PPQ failures are associated with emerging PPQ resistance in a background of artemisinin resistance. The observed connection between drug policy changes and significant reduction in PPQ susceptibility with mitigation of MQ resistance supports reintroduction of AS-MQ, in conjunction with monitoring of the P. falciparum mdr1 copy number, as a stop-gap measure in areas of DHA-PPQ failure.